Students’ Academic Self-efficacy in International Master’s Degree Programs in Finnish Universities - Kalypso Filippou (International Society for Exploring Teaching and Learning (ISETL), 2022)
This study analyzes students’ academic self-efficacy while studying in international master’s degree programs in Finland. The primary aim is to determine if students’ self-efficacy varies depending on their field of study and nationality. This study contributes to the research on students’ self-efficacy in an international academic context with a special focus on social and course performance tasks. The results indicate some variations in students’ self-efficacy, particularly in students from different fields of study. Recommendations for activities supporting students’ self-efficacy are provided based on the results of the analysis. Implications for future research, as well as limitations of the study, are discussed.